Demonstration of heterodimeric fibrinogen molecules partially conjugated with albumin in a novel dysfibrinogen: Fibrinogen Mannheim V - Dempfle, Carl-Erik; M.George, Peter; Borggrefe, Martin; Neumaier, Michael; Brennan, Stephen O. (Thrombosis and Haemostasis, 2009)
A 30-year-old female experienced three miscarriages in early pregnancy. Extensive laboratory screening showed a low plasma fibrinogen level of approximately 1 g/l detected by PT-derived fibrinogen assay.The fibrinogen level in the immunological assay was 3 g/l.The functional Clauss assay yielded an intermediate result of 1.78 g/l. During her fourth and fifth pregnancy, the patient received fibrinogen concentrates (Haemocomplettan, CLS Behring, Marburg, Germany), starting with 4 grams of human fibrinogen, followed by 2 grams every second day until the 15th week of pregnancy.The further course of these pregnancies was uneventful. SDS-PAGE and immunoblotting showed doublet bands in the positions of the high-molecular weight (HMW)-and lowmolecular-weight (LMW)-fibrinogen, a single LMW’ fibrinogen band, plus additional bands with higher molecular weight than HMW-fibrinogen, which were also reactive with anti-human serum albumin (HSA) antiserum. These bands correspond to variant fibrinogen conjugated with albumin. Reduced SDS-PAGE and immunoblotting using polyclonal anti-fibrinopeptide A antiserum disclosed one additional Aα-chain band with lower molecular weight. Amplification and sequencing of exon 5 of the α gene indicated heterozygosity for a novel single nucleotide deletion at codon Aα494 (C1537delA). His494 is replaced by Pro and this is followed by 23 (LMKLPSSTLPQLEKHSQ VSSHLC) new amino acids before premature truncation after Cys517, yielding a free C-terminal cysteine, which may link with albumin.This new fibrinogen mutation, leads to a balanced array of homo- and heterodimeric fibrinogen molecules, some of which are conjugated to albumin.
Keywords: Fibrinogen; dysfibrinogenemia; pregnancy complications; recurrent abortions